The Third International Tropical Agriculture Conference (TROPAG 2019) 2019
DOI: 10.3390/proceedings2019036029
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Zero Tillage Potato Cultivation with Different Mulch Materials in the South-Western Saline Area of Bangladesh

Abstract: Crop cultivation in the coastal saline area of Bangladesh during rabi season is limited due to late harvest of Aman rice, shorter winter period, difficulty in tillage, soil salinity, lack of fresh irrigation water etc. Zero tillage potato cultivation with mulching could minimize these obstacles and thereby increase system productivity. However, selection of mulching material is crucial for higher yield and economic return. An experiment was conducted at coastal saline area of Bangladesh during rabi 2018–19 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…W hen potato is subjected to rice straw, rice husk and compost, highest stem and root dry matter were found from rice straw (69.56 kg ha -1 ) and compost (138.92 kg ha -1 ), respectively. Rice husk produced numerically highest leaf dry matter (372.74 kg ha -1 ) and significantly lowest root dry matter (87.92 kg ha -1 ), which ultimately produced highest tuber yield (13.99 t ha -1 ) followed by rice straw (11.08 t ha -1 ) (Ali et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…W hen potato is subjected to rice straw, rice husk and compost, highest stem and root dry matter were found from rice straw (69.56 kg ha -1 ) and compost (138.92 kg ha -1 ), respectively. Rice husk produced numerically highest leaf dry matter (372.74 kg ha -1 ) and significantly lowest root dry matter (87.92 kg ha -1 ), which ultimately produced highest tuber yield (13.99 t ha -1 ) followed by rice straw (11.08 t ha -1 ) (Ali et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…According to those authors, conventional tillage used many resources (e.g., time, energy, money, and labour) and required a significant investment of labor in rice systems. At least 80% of the studies on zero-tillage with organic mulching were conducted in different regions of India, Bangladesh [36,40], China [41], and Indonesia [42] between 2000 and 2018, including one from the 1970s [43]. The area harvested under rice-potato was estimated to be around 3.02 Mha in Asia (Figure 2), based on the modeling performed in this study, around 33.6 Mha of the rice area (∼24%), which could additionally be intensified with short-duration crops such as potato during the winter season [9,17,44].…”
Section: Context and Antecedents For Moving Forward To Pztm In Asian ...mentioning
confidence: 99%
“…However, it should be noted that, to obtain a significant improvement in soil health through minimum tillage, a certain set of 3-5 years is required [76]. Sarangi et al [38] and Akkas et al [40] reported a soil salinity reduction under PZTM treatments in coastal areas (Table 2); they suggest that thiscould be caused by the reduction in soil water evaporation promoted by soil temperature reduction and moisture retention.…”
Section: Soil Health Kpimentioning
confidence: 99%